Güterverkehr in Deutschland, Europa und Übersee. Langfristige Perspektiven bis 2020. - Rommerskirchen, Stefan; Greinus, Anne; Ickert, Lutz (Deutscher Verkehrs-Verl., 2008)
Im Herbst 2007 hat die ProgTrans AG (Basel) ihren neuen "European Transport Report 2007/2008" vorgelegt - die 4. Ausgabe seit dem Jahr 2000 und zugleich die erste Ausgabe, die über den Tellerrand der EU und Europas hinausblickt. In dem Beitrag werden die zentralen Basisannahmen und Ergebnisse der Prognosen zur Güterverkehrsentwicklung in den Landverkehrsnetzen sowie zum Luftfrachtverkehr vorgestellt. Im Mittelpunkt stehen dabei Entwicklungstrends, Strukturveränderungen und Niveauvergleiche. difu

The new "European Transport Report 2007/2008" produced by ProgTrans AG (Basel) contains analysis-based data until 2006 - plus short to long-term forecasts up to 2020 - for ,,passenger and freight traffic development in a total of 37 nations in Europe and overseas. Our article deals with the above report's key assumptions and the results of the prognoses made about national transport networks' freight traffic development, air freight included, with a focus on trends in development and structural shifts and a comparison of different countries. In absolute terms, freight traffic development in Europe and in selected overseas nations shows rather notable differences also with regard to the structural changes among different modes of transport. We feel that the demand - voiced at times in the past - to separate economic output and freight traffic performance is not likely to be met in Western Europe before 2020 since it is seen as an inappropriate guiding principle with regard to transport policy-related matters. There are indications that the pressure of demand - in the areas of freight and passenger transport - will continue to escalate. Transport as such remains a fascinating field of activity for all those actively involved in formulating its future context. difu
Keywords: Verkehr; Güterverkehr; Transport; Verkehrsprognose; Verkehrsentwicklung; Mobilität; Verkehrsnachfrage; Luftverkehr; Straßenverkehr; Verkehrsnetz; Perspektive; Luftfrachtverkehr; Logistik